Redirected infection of directly biotinylated recombinant adenovirus vectors through cell surface receptors and antigens - Smith, Jeffrey S. (The National Academy of Sciences, 1999)
The inability of adenovirus to infect primitive hematopoietic cells presents an obstacle to the use of adenovirus vectors for gene transfer to these cell types. Therefore, expanding the tropism of adenovirus vectors to unique cell surface antigens would be an important development for gene therapy protocols. In this study, we sought to redirect infection of adenovirus vectors to primitive human hematopoietic cells that universally express the c-Kit receptor on their cell surface. To accomplish this, a vector was constructed by covalently linking biotin molecules to recombinant adenovirus, followed by addition of the biotinylated ligand for the c-Kit receptor, stem cell factor (SCF), through an avidin bridge. Gene transfer was directed specifically to c-Kit-positive hematopoietic cell lines, resulting in up to a 2,440-fold increase in luciferase expression with frequencies equivalent to recombinant virus infection of permissive cells. Substitution of biotinylated antibodies directed against c-Kit, CD34 (binds l-selectin), and CD44 (hyaluronate receptor) receptors for biotinylated SCF resulted in 50-, 8-, and 260-fold increases in reporter gene expression, respectively, demonstrating that infection also could be redirected through antibody–antigen interactions and through antigens other than growth factor receptors. The versatility of this vector was demonstrated further by infection of primary T cells with vectors targeted with antibodies to CD44 (resting and activated T cells) and biotinylated IL-2 (activated T cells only). Taken together, directly biotinylated adenovirus vectors represent a versatile and efficient method for redirection of virus infection to specific cells.